How Has the Introduction of New Bearing Surfaces Altered the Biological Reactions to Byproducts of Wear and Modularity? - Wooley, Paul H. (Clin Orthop Relat Res, 2014)
BACKGROUND: Biological responses to wear debris were largely elucidated in studies focused on conventional ultrahigh-molecular-weight polyethylene (UHMWPE) and some investigations of polymethymethacrylate cement and orthopaedic metals. However, newer bearing couples, in particular metal-on-metal but also ceramic-on-ceramic bearings, may induce different biological reactions. QUESTIONS/PURPOSES: Does wear debris from the newer bearing surfaces result in different biological responses compared with the known responses observed with conventional metal-on-UHMWPE bearings? METHODS: A Medline search of articles published after 1996 supplemented by a hand search of reference lists of included studies and relevant conference proceedings was conducted to identify the biological responses to orthopaedic wear debris with a focus on biological responses to wear generated from metal-on-highly crosslinked polyethylene, metal-on-metal, ceramic-on-ceramic, and ceramic-on-polyethylene bearings. Articles were selected using criteria designed to identify reports of wear debris particles and biological responses contributing to prosthesis failure. Case reports and articles focused on either clinical outcomes or tribology were excluded. A total of 83 papers met the criteria and were reviewed in detail. RESULTS: Biological response to conventional UHMWPE is regulated by the innate immune response. It is clear that the physical properties of debris (size, shape, surface topography) influence biological responses in addition to the chemical composition of the biomaterials. Highly crosslinked UHMWPE particles have the potential to alter, rather than eliminate, the biological response to conventional UHMWPE. Metal wear debris can generate elevated plasma levels of cobalt and chromium ions. These entities can provoke responses that extend to the elicitation of an acquired immune response. Wear generated from ceramic devices is significantly reduced in volume and may provide the impression of an “inert” response, but clinically relevant biological reactions do occur, including granulomatous responses in periprosthetic tissues. CONCLUSIONS: The material composition of the device, the physical form of the debris, and disease pathophysiology contribute to complex interactions that determine the outcome to all wear debris. Metal debris does appear to increase the complexity of the biological response with the addition of immunological responses (and possibly direct cellular cytotoxicity) to the inflammatory reaction provoked by wear debris in some patients. However, the introduction of highly crosslinked polyethylene and ceramic bearing surfaces shows promising signs of reducing key biological mechanisms in osteolysis.